KELEKATAN DAN KEPUASAN PERNIKAHAN PADA DEWASA AWAL DI KOTA BANDA ACEH - Putri Soraiya; Maya Khairani; Risana Rachmatan; Kartika Sari; Arum Sulistyani (Jurnal Psikologi, 2016)
Any married couple willing to have satisfaction in their marriage. However, not all couples could achievesatisfaction in their marriage. The quality of marriage was determined by three attachments style; secureattachment style, avoidant attachment style, and anxiety attachments style. This study aimed to investigate therelationship between attachment and marital satisfaction for early adulthood in Banda Aceh. This study used purposive sampling technique and selected 120 subjects (27 male and 93 female), mean of age 30.75 years old, mean of age marriage was 5-7 years, mean of children is 2. Data collected using ENRICH Marital Satisfaction (EMS) which developed by Fowers and Olson (15 statements, α= .962), and attachment scale (consist of 30items) compiled by researcher based on the theory of Hazan and Shaver (secure attachment α= .864, avoidant α= .877, anxiety α= .691). The results showed that there is a positive and significant correlation between secure attachment and marital satisfaction (rxy=.455; p =.000; p< .001). The result also showed that there is a negative and significant correlation between insecure attachment and marital satisfaction (rxy avoidant = - .460 ; p= .000; p< .001, rxy anxiety = - .231 ; p= .011; p< .05). Among the three attachment, secure attachment style has the highest significant relationship with marital satisfaction. It meant that the higher score of secure attachment style obtained, the higher satisfaction obtained by these couples.